Reconstruction of Chest Wall by Cryopreserved Sternal Allograft after Resection of Aneurysmal Bone Cyst of Sternum - Kambiz Sheikhy; Azizollah Abbasi Dezfouli; Farahnaz Sadegh Beigee (Case Reports in Surgery)
A 20-year-old female was referred to our hospital due to deformity and bulging in anterior aspect of chest wall in sternal area. Chest X-ray and CT scan confirmed a large mass with destruction of sternum. Pathologic diagnosis after incisional biopsy was compatible with aneurysmal bone cyst. We resected sternum completely and reconstructed large anterior defect by a cryopreserved sternal allograft. In follow-up of patient there was no unstability of chest wall with good cosmetic result.